Binding and reactivity in deep cavitands based on resorcin[4]arene - Petroselli, Manuel; Chen, Yong-Qing; Rebek, Jr, Julius; Yu, Yang (Green synthesis and catalysis, 2021)
A widely used class of synthetic receptors are resorcin[4]arene-based cavitands. A collection of the most representative studies in this field is reported here, from organic-soluble receptors to those that are water-soluble. Intermolecular forces involved in complex formation – hydrogen bonds, halogen bonds and solvophobic interactions – are discussed with emphasis on the relationship between guest conformation and reactivity in the cavity. The applications of hosts as reaction vessels, chaperones, templates and protecting groups in organic and aqueous media are explored, highlighting how synthetic receptors are modern tools to explore the behavior of molecules in confined spaces. This review provides an overview on deep-cavitands as synthetic receptors in organic and aqueous solution. Relation between binding orientation and reactivity in the host-guest complex is deeply discussed, pointing out the importance of intermolecular interactions and similarities with the action of biological enzymes. [Display omitted]